PHYTOCHEMICAL SCREENING, ANTIMICROBIAL AND ANTI-OXIDANT ACTIVITIES OF SALVADORA PERSICA AND CALOTROPIS GIGANTEA EXTRACTS AGAINST SELECTED PATHOGENS - HUSSAIN , A; BANO , SA; REHMAN , ZU; WAHEED , F; BASHIR , T; ALAM , S; NAWAZ , U (Biological and Clinical Sciences Research Journal, 2024)
Multiple diseases are treated using medicinal plants nowadays. Salvadora persica and Calotropis Gigantea are beneficial herbs for traditional herbal medicine. The aim of the study was to Screen phytochemicals, antibacterial and antioxidant properties of Salvadora persica and Calotropis Gigantea against Staph. Aureus, Pseudomonas aeruginosa, Escherichia coli, and Salmonella typhimurium. Methods: Phytochemicals of both Salvadora persica and Calotropis Gigantea were screened by GC-MS analyzer. Antibacterial and antioxidant activity of ethnolic and Methonolic extracts of screened phytochemicals was tested using Agar Well Diffusion and DPPH assay respectively. Salvadora persica leaf extracts (100g/ml) inhibited Staph. Aureus, Pseudomonas aeruginosa, Escherichia coli, and Salmonella typhimurium. Density was used to establish the minimal inhibitory concentration of Salvadora persica and Calotropis Gigantea extracts. Results: Both plant extracts were rich in over 250 detected chemicals via GC-MS analyzer, with 52.5% of these having antibacterial and antioxidant properties Salvadora persica extracts were characterized by 1, 8-Cineole polyphenols (45%) and cyclic ethylene mercaptole (55%), demonstrating antibacterial and antioxidant effects. Meanwhile, Calotropis Gigantea extracts contained major components Campestrol (69%) and β-tocopherol (4%). Salvadora persica and Calotropis Gigantea extracts exhibited inhibition against Pseudomonas aeruginosa at 3.12 mg/ml. Antioxidant activity, assessed via the DPPH test, revealed 35% activity with 200μl of Methanolic extracts. Both Salvadora persica and Calotropis Gigantea leaf extracts exhibited antibacterial activity against Salmonella typhimurium, Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli. Notably, Calotropis Gigantea was effective against all chosen pathogens, while Salvadora persica exclusively targeted Staphylococcus aureus. Although Calotropis Gigantea had fewer antioxidants compared to Salvadora persica, the latter’s extracts held potential for mitigating oxidative stress, aging, and related disorders. Previous studies highlighted 1, 8-Cineole polyphenols (45%) and cyclic ethylene mercaptole (55%) as antibacterial and antifungal agents against Klebsiella pneumonia and Aspergillus nigar. Conclusion: These findings underscore the promising applications of Salvadora persica and Calotropis Gigantea extracts in both antimicrobial and antioxidant interventions. And can be effected against different diseases such as Typhoid, skin diseases, and disease caused by Escherichia coli and staphylococcus aureus. Further exploration of their specific mechanisms of action and potential therapeutic applications of different metabolites and chemical compounds are warranted to harness the benefits offered by these natural extracts.